2014
DOI: 10.1111/ene.12627
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of inclusion body myositis in Norway; a population‐based clinical epidemiology study

Abstract: An estimated point prevalence of sIBM seven times higher than previously observed in Europe is reported. Our data show considerable diagnostic delay, a major challenge with new sIBM treatments in the pipeline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 31 publications
2
39
0
1
Order By: Relevance
“…In Norway, patients with IIM are followed by specialists at the public hospitals; PM and DM predominantly by rheumatologists [39], while sIBM patients are followed either by neurologists or by rheumatologists [40]. Since 1999, all patients' contacts in the specialist health service were electronically registered by 10th revised version of the International Classification of Disease (ICD-10) codes.…”
Section: Study Cohortmentioning
confidence: 99%
See 2 more Smart Citations
“…In Norway, patients with IIM are followed by specialists at the public hospitals; PM and DM predominantly by rheumatologists [39], while sIBM patients are followed either by neurologists or by rheumatologists [40]. Since 1999, all patients' contacts in the specialist health service were electronically registered by 10th revised version of the International Classification of Disease (ICD-10) codes.…”
Section: Study Cohortmentioning
confidence: 99%
“…The strategies utilised for identifying every adult patient with IIM living in south-east Norway between 2003 and 2012 (i.e., both prevalent and incident cases) have previously been described in detail [39,40]. Briefly, sequential, partly overlapping acquisition routes were utilised.…”
Section: Case Finding Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…IBM affects males more frequently (3:1), shows an overall prevalence of approximately 4‐15/1000000 (35‐71/1000000 > age 50, respectively), is noticably frequent in Western Australia, Japan, Norway, Olmsted County (Minnesota, USA), and is especially rare in Turkey and India 3, 24, 25, 26, 27, 28, 29, 30, 31. In Japan, the number of diagnosed IBM cases has steadily increased since 1991, whereas the number of PM cases has remained constant 32.…”
Section: Epidemiologymentioning
confidence: 99%
“…In Europe, the reported prevalence ranges from 4.3 x 10 -6 per million in the Netherlands, with a prevalence of 22 per million for men >50 years of age (Badrising et al, 2000), to 33 x 10 -6 in South-East Norway (Dobloug et al, 2015), while in the United States, a prevalence of 71 x 10 -6 was reported in Olmsted County (Wilson et al, 2008). There is little published data on the prevalence of the disease in Asian countries, but the condition is thought to be increasing in frequency in Japan (Suzuki et al, 2012, Nakanishi et al, 2013 and to be rare in India and Turkey (Khadilkar et al, 2008, Oflazer et al, 2011.…”
Section: Prevalence Of Ibmmentioning
confidence: 99%